2022
DOI: 10.1007/s00521-022-07394-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 forecasting and intervention planning using gated recurrent unit and evolutionary algorithm

Abstract: The rapid spread of COVID-19, caused by the SARS-CoV-2 virus, has had and continues to pose a significant threat to global health. We propose a predictive model based on the gated recurrent unit (GRU) that investigates the influence of non-pharmaceutical interventions (NPIs) on the progression of COVID-19. The proposed model is validated by case studies for multiple states in the United States. It should be noted that the proposed model can be generalized to other regions of interest. The results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“… GQ1, SQ1, SQ3, SQ4 Bi et al. ( 2022 ) USA Present a GRU-based hybrid model to predict the spread of COVID-19 across USA GQ1, GQ2, SQ1, SQ3 Bushira and Ongala ( 2021 ) Namibia Using geospatial technologies, identify and map COVID-19 risk zones and model future COVID-19 responses in Namibia. GQ1, GQ2, SQ1, SQ4 Casini and Roccetti ( 2020 ) Italy Present three computational models of increasing complexity (linear, negative binomial regression, and cognitive) to identify the one that better correlates the relationship between Italian tourist flows during the summer of 2020 and the resurgence of COVID-19 cases across the country.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… GQ1, SQ1, SQ3, SQ4 Bi et al. ( 2022 ) USA Present a GRU-based hybrid model to predict the spread of COVID-19 across USA GQ1, GQ2, SQ1, SQ3 Bushira and Ongala ( 2021 ) Namibia Using geospatial technologies, identify and map COVID-19 risk zones and model future COVID-19 responses in Namibia. GQ1, GQ2, SQ1, SQ4 Casini and Roccetti ( 2020 ) Italy Present three computational models of increasing complexity (linear, negative binomial regression, and cognitive) to identify the one that better correlates the relationship between Italian tourist flows during the summer of 2020 and the resurgence of COVID-19 cases across the country.…”
Section: Resultsmentioning
confidence: 99%
“… 2022 ; Bi et al. 2022 )
Fig. 10 Question for domain 2 GRADE assessment: ML prediction compared to real geographic location for tracking COVID-19 pandemics critical geolocations: ( a ) Ozik et al 2021 have no outcomes for cumulative COVID-19 cases’ prediction.
…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Bi, Fili and Hu [10] tested the performance of GRU against other models for 6-, 12-, 18-, 24-and 30-day periods. It was found that GRU outperformed LASSO for all but the 6-day prediction with a MAE that ranged from 19.62% to 32.72% whilst LASSO ' s MAE was between 25.71% and 42.85%.…”
Section: Performance Of Deep Learning Modelsmentioning
confidence: 99%
“…The approach to forecasting the number of patients involves various machine learning techniques to discover the pattern of epidemic data. Various techniques have been used, such as Support Vector Regression [6], Deep Learning models including Recurrent Neural Network (RNN), [7] Gated Recurrent Unit (GRU) [8], Long Short-Term Memory (LSTM) [9], and others. The goal of this study is to use machine learning for analyzing and predicting the number of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%